Coronavirus Disease-2019: Knowledge, Attitude, and Practices of Health Care Workers at Makerere University Teaching Hospitals, Uganda - Olum, Ronald; Chekwech, Gaudencia; Wekha, Godfrey; Nassozi, Dianah Rhoda; Bongomin, Felix (Frontiers in public health, 2020)
Coronavirus disease-2019 (COVID-19) is an emerging public health problem threatening the life of over 2.4 million people globally. The present study sought to determine knowledge, attitude and practices (KAP) of health care workers (HCWs) toward COVID-19 in Makerere University Teaching Hospitals (MUTHs) in Uganda. An online cross sectional, descriptive study was undertaken through WhatsApp Messenger among HCWs in four MUTHs. HCWs aged 18 years and above constituted the study population. KAP toward COVID-19 was assessed by using a pre-validated questionnaire. Bloom's cut-off of 80% was used to determine sufficient knowledge (≥80%), positive attitude (≥4), and good practice (≥2.4). All analyses were performed using STATA 15.1 and GraphPad Prism 8.3. Of the 581 HCWs approached, 136 (23%) responded. A vast majority of the participants were male ( = 87, = 64%), with a median age of 32 (range: 20-66) years. Eighty-four (62%) were medical doctors and 125 (92%) had at least a bachelor's degree. Overall, 69% ( = 94) had sufficient knowledge, 21% ( = 29) had positive attitude, and 74% ( = 101) had good practices toward COVID-19. Factors associated with knowledge were age >40 years (aOR: 0.3; 95% CI: 0.1-1.0; = 0.047) and news media (aOR: 4.8; 95% CI: 1.4-17.0; = 0.015). Factors associated with good practices were age 40 years or more (aOR: 48.4; 95% CI: 3.1-742.9; = 0.005) and holding a diploma (aOR: 18.4; 95% CI: 1-322.9; = 0.046). Continued professional education is advised among HCWs in Uganda to improve knowledge of HCWs hence averting negative attitudes and promoting positive preventive and therapeutic practices. We recommend follow up studies involving teaching and non-teaching hospitals across the country.